2001
DOI: 10.1111/j.1749-6632.2001.tb03835.x
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Immune System with Specific Reference to Membrane Encapsulation and Islet Transplantation

Abstract: The concept of immunoisolation by use of a bioartificial membrane is discussed, concentrating on the immunological mechanisms that are likely to be operative in the light of recent information on the workings of the immune system. Special attention is given to the use of encapsulation for the purpose of treating autoimmune diabetes by implantation of xenogeneic islet tissue. It is argued that the term immunoisolation is misleading because the immune system is always activated by the indirect pathway of antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Local attraction of macrophages by shedding is more apparent for xenografts than for allografts, since virtually every protein shed by a xenograft is different from the host [52,54,55]. Xenogenic antigen release, especially the release of ␣-1,3-galactose, attracts and activates macrophages, which in turn release cytokines such as Il-1␤, TNF-␣, and IFN-␥, but also nitric oxide and oxygen radicals [54,56]. These macrophage-derived factors are small enough to pass the semipermeable membrane of microcapsules and may well affect encapsulated islet graft function and vitality.…”
Section: Biocompatibilitymentioning
confidence: 99%
“…Local attraction of macrophages by shedding is more apparent for xenografts than for allografts, since virtually every protein shed by a xenograft is different from the host [52,54,55]. Xenogenic antigen release, especially the release of ␣-1,3-galactose, attracts and activates macrophages, which in turn release cytokines such as Il-1␤, TNF-␣, and IFN-␥, but also nitric oxide and oxygen radicals [54,56]. These macrophage-derived factors are small enough to pass the semipermeable membrane of microcapsules and may well affect encapsulated islet graft function and vitality.…”
Section: Biocompatibilitymentioning
confidence: 99%
“…This mechanism, however, has only a minor impact on encapsulated grafted cells because the membrane physically separates donor cells from recipient cells [26] . Humoral rejection does not require celltocell contact and is operable via mechanisms activated by the indirect recognition pathway.…”
Section: The Immune Barriermentioning
confidence: 99%
“…Although alginate capsules can insulate cells from contact and attack by immune cells, immune reaction may still occur through humoral route by the release of cell debris (Calafiore et al 1997, Siebers et al 1997. It has been speculated that the failure of islet transplantation could be attributable to several factors including erforin, cytokines, nitric oxide, poor nutrition, and hypoxia (Siebers et al 1999, Gray 2001, de Groot et al 2003, 2004. Indeed, our study found that at least 12 cytokines were increased to different degrees in the peritoneal fluid of capsule-implanted mice.…”
Section: Discussionmentioning
confidence: 60%